The Impact of a Southern Ocean Cyclonic Eddy on Mesopelagic Micronekton. Issue 11 (11th November 2022) - Della Penna, Alice; Llort, Joan; Moreau, Sebastien; Patel, Ramkrushnbhai; Kloser, Rudy; Gaube, Peter; Strutton, Peter; Boyd, Philip W.
Abstract: Mesoscale eddies shape the foraging ecology of predators such as marine mammals and seabirds. A growing number of animal tracking studies show that predators alter their swimming, diving, and foraging behavior within mesoscale eddies. However, little is known about how Southern Ocean eddies influence the distribution of mesopelagic micronekton (fish, squid, and crustaceans), which are major prey items of megafauna. Studies in other oceanic regions have found that eddies can influence the abundance and community composition of micronekton. Here, we analyze acoustic observations from a 14‐day survey of a cyclonic mesoscale eddy, its surrounding waters, and the Polar Frontal Zone (PFZ) waters where the eddy formed. We report and interpret spatial patterns of acoustic backscatter at 18 and 75 kHz, proxies indicating combined changes in species, size, and abundance of micronekton. We find that the vertical distribution of acoustic backscatter matched the underwater light conditions characteristic of the eddy core, periphery, and surrounding waters, at scales smaller than 10 km. The median water‐column integrated acoustic backscatter values in the eddy core were only half of those measured in the Sub‐Antarctic Zone waters surrounding the eddy, but similar to those measured in the PFZ, where the eddy originated 27 days prior. These results suggest that, as for physical and chemical tracers, the eddy maintained its biological characteristics from its source waters creating a unique habitat compared to its surroundings. Plain Language Summary: Mesoscale eddies are rotating currents that are everywhere in the ocean. They are typically tens to one or two hundred km across, with lifetimes spanning weeks to months. Mesoscale eddies have a dramatic impact on the patterns of primary production in the open ocean, the transport of heat and salt across oceanic regions, global biogeochemical cycles, and the feeding behavior of marine predators such as pinnipeds, sharks, billfishes, and seabirds. In this study, we used underwater acoustic measurements to evaluate the effects of a Southern Ocean mesoscale eddy on the distribution of deep water micronekton, a diverse group of small animals including fish, crustacea, and squids. We found that the abundance and vertical distribution of micronekton inside the eddy differed from the surrounding waters. Micronekton distribution was instead more similar to where the eddy had originated a month prior to our sampling. Our results suggest that mesoscale eddies can maintain their biological characteristics from their source waters, creating a unique habitat compared to surrounding waters. Key Points: We observed the distribution of acoustic backscatter in the mesopelagic zone across a Southern Ocean cyclonic eddy The integrated and vertical distribution of the acoustic backscatter inside the eddy were similar to its origin waters The eddy presented a unique habitat compared to its surrounding waters, affecting the accessibility of mesopelagic prey to diving predators